HUBUNGAN PENGETAHUAN TENTANG PEMBATASAN ASUPAN CAIRAN DENGAN SELF CARE MANAGEMENT PASIEN HEMODIALISIS DI RS ROEMANI SEMARANG - Adibah Salsabila; Merry Tiyas Anggraini (Jurnal Kesehatan, 2025)
Chronic kidney disease patients require lifelong hemodialysis therapy. Self care management is needed to improve quality of life and prevent complications. Knowledge about fluid intake restriction is needed as one of the factors to achieve good self-care management. This study aims to determine the relationship between knowledge about fluid intake restriction and self-care management in hemodialysis patients at Roemani Semarang Hospital. Analytic observational with cross sectional design was the method in this study. The study population was hemodialysis patients at Roemani Semarang Hospital as of May 2023 and the sample that met the inclusion criteria amounted to 83 people and the sampling technique used total sampling. Data were collected using a knowledge questionnaire about fluid intake restriction and a self-care management questionnaire. Data analysis using the spearman rank test. Based on the Spearman rank correlation test, the p value = 0.001 and the correlation strength of +0.699 means a strong relationship between knowledge about fluid intake restrictions and self-care management of hemodialysis patients with a positive relationship direction. The better the knowledge about fluid intake restriction, the higher the self-care management of hemodialysis patients at Roemani Semarang Hospital.